Mass customization:the case study of Jiangxi Boyun Company - Gong, Mengfeng (2011)
Abstract Mass customization (MC) has been paid more attention by the market in recent year. However, not all the industries can mass customization very well. This dissertation presents an overview of MC and show the concept through case study of Jiangxi Boyun Company (JBC).